Forward osmosis membranes: the significant roles of selective layer - Tian, Miao (2023)
Forward osmosis (FO) is a promising separation technology to overcome the challenges of pressure-driven membrane processes. The FO process has demonstrated profound advantages in treating feeds with high salinity and viscosity in applications such as brine treatment and food processing. This review discusses the advancement of FO membranes and the key membrane properties that are important in real applications. The membrane substrates have been the focus of the majority of FO membrane studies to reduce internal concentration polarization. However, the separation layer is critical in selecting the suitable FO membranes as the feed solute rejection and draw solute back diffusion are important considerations in designing large-scale FO processes. In this review, emphasis is placed on developing FO membrane selective layers with a high selectivity. The effects of porous FO substrates in synthesizing high-performance polyamide selective layer and strategies to overcome the substrate constraints are discussed. The role of interlayer in selective layer synthesis and the benefits of nanomaterial incorporation will also be reviewed.